Effect of Flax Seeds (Linum usitatissimum L.) Extract in Male Reproductive System of Albino Rat Treated with Cyproterone Acetate - Maysaa Adil Hadi (Journal of Global Pharma Technology, 2017)
The purpose of this report to assess the possible protective effects of 20%methanolic extract of flax seeds on cyproterone acetate mediated reproductive dysfunction of adult albino rats. Albino rats (35) place din a random manner into 7 groups, 5 rats in each. The normal control rat was the first group, while the second control group was given corn oil. Third group received cyproterone acetate (CPA) (10 mg/kg) as (positive control). Fourth and fifth groups were treated with 250&500mg/kg of flaxseeds extract respectively. The other protected sixth and seventh groups received CPA (10mg/kg) with flaxseeds extract 250 and 500 mg/kg respectively. All groups treated for 50 days orally by gavages tube. In CPA group, the outcome displayed significant reduction (P≤0.05) in the body weight, sperm parameters and FSH level, a significant raise (P≤0.05) in sperms abnormality and level of testosterone, and non-significant decline (P˃0.05) in reproductive organs and the accessory glands/ body weight ratios and LH level as compared to oil control. Treatment with flaxseeds 250&500 mg/kg caused decrease in the body weight but it considered as significant raise(P≤0.05)in comparison with CPA group, while group treated with flaxseeds extract 250 mg/kg make on-significant changes (P˃0.05) in each of reproductive organs and accessory gland/body weight ratios, LH level record non-significant decrease (P˃0.05) and significant decrease(P≤0.05) in testosterone level as compared to control D.W and CPA group whereas treatment with flaxseeds extract 500 mg/kg recorded significant increase in testes and epididymis/body weight ratio as compared to D.W, corn oil controls, and CPA groups. Furthermore, oral administration of the flaxseeds extract with CPA at two doses 250 & 500 mg/kg with CPA could reduce the negative effect of CPA in the body weight but it could not enhance the most of the sperm parameters and histological changes of both testes and epididymis caused by CPA. In conclusion, CPA (10mg/kg)induce degenerative changes in the reproductive organs of male rats and the 20%methanolic extract of flaxseeds were exhibit similar effect of CPA but at less extent in the male reproductive system.Keywords: Flax seeds (linum usitatissimum L.), Cyproterone Acetate, Reproductive Male system, Albino Rat.